HPV immunisation and cervical screening—confirmation of changed performance of cytology as a screening test in immunised women: a retrospective population-based cohort study - Palmer, T J; McFadden, M; Pollock, K G J; Kavanagh, K; Cuschieri, K; Cruickshank, M; Cotton, S; Nicoll, S; Robertson, C (British journal of cancer, 2016)
Background: To document the effect of bivalent HPV immunisation on cervical cytology as a screening test and assess the implications of any change, using a retrospective analysis of routinely collected data from the Scottish Cervical Screening Programme (SCSP). Methods: Data were extracted from the Scottish Cervical Call Recall System (SCCRS), the Scottish Population Register and the Scottish Index of Multiple Deprivation. A total of 95 876 cytology records with 2226 linked histology records from women born between 1 January 1988 and 30 September 1993 were assessed. Women born in or after 1990 were eligible for the national catch-up programme of HPV immunisation. The performance of cervical cytology as a screening test was evaluated using the key performance indicators used routinely in the English and Scottish Cervical Screening Programmes (NHSCSP and SCSP), and related to vaccination status. Results: Significant reductions in positive predictive value (16%) and abnormal predictive value (63%) for CIN2+ and the mean colposcopy score (18%) were observed. A significant increase (38%) in the number of women who had to be referred to colposcopy to detect one case of CIN2+ was shown. The negative predictive value of negative- or low-grade cytology for CIN2+ increased significantly (12%). Sensitivity and specificity, as used by the UK cervical screening programmes, were maintained. Conclusions: The lower incidence of disease in vaccinated women alters the key performance indicators of cervical cytology used to monitor the quality of the screening programme. These findings have implications for screening, colposcopy referral criteria, colposcopy practice and histology reporting.